2016
DOI: 10.2196/jmir.5112
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based and Mobile Stress Management Intervention for Employees: A Randomized Controlled Trial

Abstract: BackgroundWork-related stress is highly prevalent among employees and is associated with adverse mental health consequences. Web-based interventions offer the opportunity to deliver effective solutions on a large scale; however, the evidence is limited and the results conflicting.ObjectiveThis randomized controlled trial evaluated the efficacy of guided Web- and mobile-based stress management training for employees.MethodsA total of 264 employees with elevated symptoms of stress (Perceived Stress Scale-10, PSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
6
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 195 publications
(192 citation statements)
references
References 61 publications
9
171
6
6
Order By: Relevance
“…Thus, the present study provides further evidence that CBT-based interventions can have enduring effects that go beyond immediate short-term effects, and can also prevent further aggravation of symptoms. Remarkably, the effect sizes for most outcomes were similar to those found in the pilot-evaluation study of the novel intervention (23). Thus, the present study replicated the results of this study in a large-scale randomized controlled trial.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the present study provides further evidence that CBT-based interventions can have enduring effects that go beyond immediate short-term effects, and can also prevent further aggravation of symptoms. Remarkably, the effect sizes for most outcomes were similar to those found in the pilot-evaluation study of the novel intervention (23). Thus, the present study replicated the results of this study in a large-scale randomized controlled trial.…”
Section: Discussionsupporting
confidence: 86%
“…So far, randomized controlled trials (RCT) on internet-based SMI show mixed results with some studies reporting significant results with moderate effects sizes on perceived stress (17)(18)(19) and others yielding non-significant outcomes (20,21). Our group recently conducted a RCT testing the efficacy of an internet-based stress management intervention (iSMI) among employees with heightened levels of perceived stress (22,23). The intervention proved to be effective in reducing perceived stress and other mental and work-related health outcomes.…”
mentioning
confidence: 99%
“…This might indicate that individuals with stressful lives have problems to adhere to fixed synchronous therapy sessions, and providing asynchronous treatments might help them to get access to psychological treatments, which they would otherwise not utilize. Such an assumption is supported by studies that found high proportions of first-time helpseekers in internet-based stress management programs [76][77][78][79][80]. However, future research is needed to confirm such an assumption.…”
Section: Preference For Specific Delivery Formatsmentioning
confidence: 94%
“…A recent meta-analysis found that these interventions are effective in increasing psychological wellbeing and workplace effectiveness but that the mean intervention completion (the extent to which participants adhered to the intervention) was 45% with a range of 3% to 95% [17]. Although there are examples of occupational digital mental health interventions that have achieved good adherence [18][19][20][21], uptake of and engagement with these interventions in the workplace clearly remains a pressing concern.…”
Section: Introductionmentioning
confidence: 99%